LIVING ARRANGEMENTS OF THE OLD IN CONTEXT OF MODERNIZATION- A STUDY OF THE ELDERLY WOMEN IN KERALA - JACOB JOHN KATTAKAYAM
By 2021 the growth rate of elderly persons in Kerala will be one and a half times higher than the growth rate of general population. Most of the states in India including Kerala have not decided on Old Age Policy though the Qovernment of India has formed a National Policy on Older Persons in 1999. The growing elderly population is a threat to the socioeconomic conditions of the State. One consolation is that the elderly themselves are doing a purposeful socialization for themselves. Now the trend is that the elderly do a lot of mental exercises on various patterns of living arrangements and then choose best according to the socioeconomic conditions.